2003
DOI: 10.1002/pssb.200301669
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline soft magnetic materials: intergrain coupling and spin freezing effects

Abstract: The static and dynamic magnetic properties of the nanocrystalline soft magnetic FeNbB alloys consisting of Fe-nanograins embedded in an amorphous matrix were investigated by means of dc and ac susceptibility, magnetization and hysteresis loop measurements in a wide temperature range. We show that these alloys exhibit particular complex magnetic behaviour versus temperature. The spin-glass like behaviour at cryogenic temperatures is followed by a very soft magnetic behaviour at intermediate temperatures, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The interface of the nanoparticles due to the complex magnetic structure seems to be able to tilt the magnetic moment of the nanoparticles from the parallel direction offered by the external magnetic field. Such influences were reported, observing the increase of coercivity at low temperatures, by Skorvanek et al [15,16]. The authors relate this behaviour and also the observed creep to magnetic moments of the nanocrystalline grains and highly distorted interfaces frozen in their random anisotropy orientations.…”
Section: Summary and Discussionsupporting
confidence: 55%
“…The interface of the nanoparticles due to the complex magnetic structure seems to be able to tilt the magnetic moment of the nanoparticles from the parallel direction offered by the external magnetic field. Such influences were reported, observing the increase of coercivity at low temperatures, by Skorvanek et al [15,16]. The authors relate this behaviour and also the observed creep to magnetic moments of the nanocrystalline grains and highly distorted interfaces frozen in their random anisotropy orientations.…”
Section: Summary and Discussionsupporting
confidence: 55%
“…As a result, a nanocrystalline structure of ferromagnetic nanocrystals embedded in a ferromagnetic amorphous matrix with magnetic correlation length larger than mean grain size is obtained. The random anisotropy model extended by Herzer [13] explained that when grain dimensions are kept below the ferromagnetic exchange length, the anisotropic of the homogenously distributed nanocrystals continues to average out [14]. In addition, this composite structure leads to the compensation of l s between the amorphous (positive contribution) and the crystalline (negative contribution) phases, decreasing the magnetoelastic energy.…”
Section: Annealed Ribbons At 540 1cmentioning
confidence: 99%